2020
DOI: 10.26502/acmcr.96550248
|View full text |Cite
|
Sign up to set email alerts
|

Viral Integration Analysis Reveals Likely Common Clonal Origin of Bilateral HPV16-Positive, p16-Positive Tonsil Tumors

Abstract: Infections with high-risk human papilloma viruses (HPV) are responsible for a significant number of oropharyngeal squamous cell carcinoma (OPSCC), with infection rates currently rising at epidemic rates in the western world. Synchronous bilateral HPV+ tumors of both tonsils are a very rare event whose understanding, however, could provide important insights into virus-driven tumor development and progression and whether such integration events are of clonal origin. In this study we analyzed a single case of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Viral‐host fusion transcripts have been reported by other groups to increase E6/E7 expression 18‐20 . Previous work from our group has shown that viral‐cellular fusion transcripts may or may not form depending on the location of the integration site within the gene (within an intron vs exon) 20,30,43 . It is possible that some integrations within introns are spliced out and therefore do not produce a fusion transcript, while others may alter splice acceptor/donor sites such that they are retained at the transcript level.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Viral‐host fusion transcripts have been reported by other groups to increase E6/E7 expression 18‐20 . Previous work from our group has shown that viral‐cellular fusion transcripts may or may not form depending on the location of the integration site within the gene (within an intron vs exon) 20,30,43 . It is possible that some integrations within introns are spliced out and therefore do not produce a fusion transcript, while others may alter splice acceptor/donor sites such that they are retained at the transcript level.…”
Section: Discussionmentioning
confidence: 93%
“…[18][19][20] Previous work from our group has shown that viral-cellular fusion transcripts may or may not form depending on the location of the integration site within the gene (within an intron vs exon). 20,30,43 It is possible that some integrations within introns are spliced out and therefore do not produce a fusion transcript, while others may alter splice acceptor/donor sites such that they are retained at the transcript level. We attempted to amplify the predicted fusion transcripts based on the DNA-level information we obtained from DIPS-PCR in six samples but were only successful in amplifying the fusion in one sample (BMT-1159).…”
Section: F I G U R E 7 Kaplan-meier Curves Of Oropharynx Patients Sepmentioning
confidence: 99%
“…An interesting finding using HPV integration detection for studying the clonal relationship between bilaterally developing TSCCs was reported by Pinatti et al [68]. In a case study, six integration events were detected by DIPS-PCR, including two intragenic events in the genes CD36, involved in fatty acid import and LAMA3, involved in cell adhesion, migration and differentiation of keratinocytes.…”
Section: Loci Of Hpv Integration In the Human Genomementioning
confidence: 86%
“…Both TRAF3 and CYLD play a role in both negatively regulating NF-κB canonical and noncanonical pathways while simultaneously stimulating a potent and first-line antiviral response through type I IFN signaling. Mutations in these genes will therefore lead to constitutive activation of NF-κB, which promotes cell survival and an impaired innate immunity against viral infections [68,95,96]. Moreover, it is suggested that maintenance of episomal HPV even pressures cells to mutate TRAF3/CYLD.…”
Section: Deregulated Expression Of Human Genes By Hpv Integrationmentioning
confidence: 99%
“…In contrast to the two distinct karyotypes seen in our patient, Pinatti et al suggested a common origin of a tumor in their case report on an HPV+ p16+ bilateral TSCC. 7 Through analysis of HPV integration events, the authors ultimately supported single‐clone hypothesis of bilateral tumor development, although, again, no differing histopathological specimens were noted between tonsils. More generally, all three hypotheses of bilateral tonsillar carcinoma origin have validity and the weight of their respective contribution varies on a case‐by‐case basis.…”
Section: Discussionmentioning
confidence: 83%